2015
DOI: 10.1089/fpd.2014.1850
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus ST6-t701 Isolates from Food-Poisoning Outbreaks (2006–2013) in Xi'an, China

Abstract: The aim of the study was to investigate the molecular epidemiologic of Staphylococcus aureus isolated from seven staphylococcal food-poisoning (SFP) outbreaks between 2006 and 2013 in Xi'an, northwest China. A total of seven S. aureus isolates associated with seven SFP outbreaks were obtained and characterized by determining the multilocus sequence typing, spa typing, pulsed-field gel electrophoresis (PFGE), antimicrobial susceptibility, toxin and resistant genes. The results showed that S. aureus ST6-t701 (71… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 10 publications
3
24
1
1
Order By: Relevance
“…The hybridization pattern of the isolate was identical to the predicted hybridization pattern for clinical CC6-MSSA isolates 394_SAUR (GenBank JVIV) and C9 (GenBank LDVH). It harbored the beta-lactamase operon as well as the IEC genes sea , sak and scn .CC6 has been recovered occasionally from humans including butchers [117] and it has been implicated in episodes of food-poisoning [118]. It was previously identified in camels from Dubai, where it carried a different sea allele [21], as well as in non-human primates and various domestic animals [4,119].…”
Section: Resultsmentioning
confidence: 99%
“…The hybridization pattern of the isolate was identical to the predicted hybridization pattern for clinical CC6-MSSA isolates 394_SAUR (GenBank JVIV) and C9 (GenBank LDVH). It harbored the beta-lactamase operon as well as the IEC genes sea , sak and scn .CC6 has been recovered occasionally from humans including butchers [117] and it has been implicated in episodes of food-poisoning [118]. It was previously identified in camels from Dubai, where it carried a different sea allele [21], as well as in non-human primates and various domestic animals [4,119].…”
Section: Resultsmentioning
confidence: 99%
“…The involvement of see in food poisoning has rarely been reported in China. However, three cases of food poisoning caused by SEE were reported in USA, France (Bergdoll et al, 1971; Morris et al, 1972) and Shaanxi, China (Li et al, 2015). Similarly, Ostyn et al (2010) reported that 90 ng of SEE can lead to food poisoning.…”
Section: Discussionmentioning
confidence: 99%
“…Fibronectin-binding proteins have been shown to have important roles in the establishment of infections and persistent infections; α -hemolysin leads to disruption of the epithelial barrier and homeostasis, which in turn lead to necrotic cell death and systemic infection (Kong et al, 2016); and PVL is a pore-forming cytotoxin. Notably, the hlα gene was reported to be responsible for an S. aureus food poisoning outbreak in Xi’an, China (Li et al, 2015). Indeed, approximately 90.0% of S. aureus induced necrotizing pneumonia is associated with isolation of S. aureus strains carrying the pvl gene (Bhatta et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Out of 60 isolates, 9 (15%) were positive for the PCR amplicon of 310 bp for hlb gene and 7 (11.67%) were positive for the amplicon of 938 bp for hlg (Figure 3). Li et al (2015) reported that food poisoning outbreaks in China were caused by hla and hld genes.…”
Section: Resultsmentioning
confidence: 99%